Analysis of personal data-sharing consent factors, with focus on loyalty programs in the Czech Republic - Formanek, Tomas; Tahal, Radek (Business: Theory and Practice, 2018)
The purpose of this study is to provide structured, topical and representative analysis of personal data sharing preferences in the Czech Republic. Within the context of personal data sharing and protection, we focus on profiling individuals who voluntarily share their personal data with good-faith corporate entities. Loyalty program operators serve as a common and representative model of commercially driven collection and processing of personal data. We address different types of personal data and factors affecting individual data-sharing consent. Our original research is based on primary surveyed data (806 respondents surveyed during 2017). Multiple quantitative methods such as hierarchical clustering and logistic regression are employed in the analysis. Also, an important part of our research is based on evaluation of structured in-depth interviews, focused on personal data sharing and protection topics. We find pronounced socio-demographic differences in individual propensity to share one’s personal data with commercial data processors. Main findings and contrasting factors are pointed out and discussed within the paper. Our analysis reflects the needs of academic and corporate researches to whom it provides actionable and stratified results, especially in context of the new EU legislation: the GDPR directive on personal data protection.